Nuevos datos de la flora cantábrica - Nava Fernández, Herminio S.; Fernández Casado, Mª Ángeles; Martino, Juana (Lazaroa, 1995)
Se dan noticias de 12 taxones nuevos o poco conocidos de Asturias, León y Cantabria.